Sesquiterpene lactones-enriched fractions from Xanthium mongolicum Kitag alleviate RA by regulating M1 macrophage polarization via NF-κB and MAPK signaling pathway - Han, Jing; Wang, Jingwen; Wang, Yicun; Zhu, Zhiqi; Zhang, Siwang; Wu, Bingrong; Meng, Mingsong; Zhao, Jianning; Wang, Dongsheng (Frontiers in Pharmacology, 2023)
Rheumatoid arthritis (RA) is a chronic autoimmune disease, characterized by activated M1-like macrophage in the joint. Xanthium mongolicum Kitag (X. mongolicum) is a traditional medicinal plant that has long been used to treat RA and other immune diseases in China. The aim of this study was to isolate the main anti-RA components of the plant, explore their anti-RA activity and potential mechanisms in vitro and in vivo. Fractions of X. mongolicum were separated based on polarity. Anti-RA activity of the fractions were screened by LPS-stimulated RAW264.7 macrophage in vitro. The major active compounds were identified by UPLC-MS and quantified by HPLC. The anti-RA effects of the active fraction was evaluated in complete freund’s adjuvant (CFA)-induced arthritis and collagen-induced arthritis (CIA) mouse models in vivo and LPS-stimulated macrophage in vitro. Sesquiterpene lactones-enriched fraction from X. mongolicum (SL-XM) exhibited the strongest anti-RA activity among all components in vitro. Five major constituents i.e., Xanthinosin (1), Xanthatin (2), Mogolide D (3), Mogolide E (4), and Mogolide A (5) were identified as major compounds of SL-XM. SL-XM ameliorated symptoms of CFA and CIA induced arthritis mice model. Furthermore, SL-XM treatment inhibited LPS-induced M1 macrophages polarization. In addition, SL-XM inhibited the phosphorylation of NF-κB and MAPK signaling pathways in LPS-induced macrophage and CIA-challenged mice. The main anti-RA active fraction of X. mongolicum may be the Sesquiterpene lactones, which includes five key compounds. SL-XM may exert its anti-RA effect by suppressing M1 macrophage polarization via the NF-κB and MAPK signaling pathway.